2004
DOI: 10.1080/15622970410029936
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of brain-derived neurotrophic factor (BDNF) gene Val66Met polymorphism in schizophrenia and bipolar affective disorder

Abstract: Brain-derived neurotrophic factor (BDNF) has been implicated in the pathogenesis of schizophrenia and bipolar disorder. A functional polymorphism Val66Met of BDNF gene was studied in patients with schizophrenia (n=336), bipolar affective disorder (n=352) and healthy controls (n=375). Consensus diagnosis by at least two psychiatrists, according to DSM-IV and ICD-10 criteria, was made for each patient using a structured clinical interview for DSM-IV Axis I disorders (SCID). No association was found between the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
52
3
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 54 publications
3
52
3
3
Order By: Relevance
“…31 In spite of this evidence, other investigators have not been able to replicate these findings in case-control association studies. [32][33][34][35][36][37][38] In the case of MDD, some studies reported a negative association of the Val66Met BDNF polymorphism, 33,39,40 while other studies have found a haplotype containing this variant to be positively associated to the MDD phenotype. 41,42 Moreover, positive associations of this single SNP and a haplotype containing it have been reported to be associated to childhood-onset mood disorder 41,43 as well as geriatric depression.…”
Section: Introductionmentioning
confidence: 99%
“…31 In spite of this evidence, other investigators have not been able to replicate these findings in case-control association studies. [32][33][34][35][36][37][38] In the case of MDD, some studies reported a negative association of the Val66Met BDNF polymorphism, 33,39,40 while other studies have found a haplotype containing this variant to be positively associated to the MDD phenotype. 41,42 Moreover, positive associations of this single SNP and a haplotype containing it have been reported to be associated to childhood-onset mood disorder 41,43 as well as geriatric depression.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have associated this polymorphism with increased susceptibility to anorexia nervosa (Ribases et al, 2003), obsessive-compulsive disorders (Hall et al, 2003), eating disorders (Friedel et al, 2005), depression (Sen et al, 2003), schizophrenia (Skibinska et al, 2004), Alzheimer's disease (Ventriglia et al, 2002), and Parkinson's disease (Momose et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These include BDNF, which showed evidence for association with bipolar disorder in two cohorts of predominantly Caucasian origin, 15,16 although this has not been replicated in several other cohorts of European and Japanese origin. [17][18][19][20] Association and functional studies have also implicated the XBP1 gene in bipolar susceptibility, 21 but again, this has not been replicated in cohorts of European and Chinese origin. 22,23 Evidence has also been reported for association of the GRIN1 gene with bipolar disorder in a cohort of predominantly European Caucasian origin.…”
Section: Introductionmentioning
confidence: 99%